Dystocia due to Breech presentation with cranio -skeletal malformations in a crossbred cow - S, Rajasokkappan; S, Rajan; T, Govindarasu; R P, Nisha; T, Suganya (Indian Journal of Veterinary Medicine, 2024)
A third calving full term pregnant Jersey cross bred cattle was presented to Veterinary Poly Clinic with the history of calving difficulty. All the vital sign parameters of the Dam were within the normal limits. The animal is on sternal recumbency. Upon vaginal examination, it was found that the cervix was fully dilated. Additionally, a breech presentation was observed. Detailed vaginal examination and manipulations the calf was brought to extended position of hind legs. Then by careful assistance hind limb was dragged outside then the calf's hip and thigh region were locked at the pelvic brim of the dam, making delivery difficult. Despite ample lubrication, a bulldog calf with cranio-skeletal malformations was delivered. These malformations are attributed to hereditary causes, primarily driven by recessive autosomal genes. The communication highlights the importance of understanding genetic predispositions and conducting thorough examinations during pregnancy to detect such anomalies early. It also emphasizes the need for careful breeding practices to minimize the risk of inherited disorders in livestock populations.